Creative strategies at work: theoretical proposition and validation of psychometric measure - Moraes, Melissa Machado de; Lima, Suzana Maria Valle (Paidéia (Ribeirão Preto), 2009)
There is little empirical research about creativity at the workplace in Brazil, despite the topic's relevance. This study aimed to present a theoretical proposition and psychometric validation of a measure of creative strategies at work. Such construct refers to the efforts individuals exert so to favor the creation of new and useful ideas focused on work problem solving. Data were collected via Internet in a Brazilian governmental organization in a sample of 688 employees. Exploratory factor analysis was conducted and the found hierarchical factor solution for creative strategies is composed of 44 items distributed in five first-order factors (a=.75 to .95), one with two facets, and all of them are grouped into a single higher-order factor. Results indicate the proposed measure is adequate and can greatly contribute to the advancement of research on creativity at the workplace and indicate directions to refine the measure.